Carbon isotopic evidence for microbial control of carbon supply to Orca Basin at the seawater-brine interface - Shah, S. R.; Joye, S. B.; Brandes, J. A.; McNichol, A. P. (BIOGEOSCIENCES, 2013)
Orca Basin, an intraslope basin on the Texas-Louisiana continental slope, hosts a hypersaline, anoxic brine in its lowermost 200m in which limited microbial activity has been reported. This brine contains a large reservoir of reduced and aged carbon, and appears to be stable at decadal time scales: concentrations and isotopic composition of dissolved inorganic (DIC) and organic carbon (DOC) are similar to measurements made in the 1970s. Both DIC and DOC are more ``aged{''} within the brine pool than in overlying water, and the isotopic contrast between brine carbon and seawater carbon is much greater for DIC than DOC. While the stable carbon isotopic composition of brine DIC points towards a combination of methane and organic carbon remineralization as its source, radiocarbon and box model results point to the brine interface as the major source region for DIC, allowing for only limited oxidation of methane diffusing upwards from sediments. This conclusion is consistent with previous studies that identify the seawater-brine interface as the focus of microbial activity associated with Orca Basin brine. Isotopic similarities between DIC and DOC suggest a different relationship between these two carbon reservoirs than is typically observed in deep ocean basins. Radiocarbon values implicate the seawater-brine interface region as the likely source region for DOC to the brine as well as DIC.

Radiocarbon and stable isotope geochemistry of organic matter in the Amazon headwaters, Peruvian Andes - Townsend-Small, A.; Noguera, J. L.; McClain, M. E.; Brandes, J. A. (Global Biogeochemical Cycles, 2007)
[1] We used delta C-13, delta N-15, and Delta C-14 to determine the sources of riverine organic matter in the Pozuzo River, a tributary of the Pachitea River located in the mountainous headwaters of the Amazon. Particulate organic matter (POM) Delta C-14 decreased downstream, suggesting that young organic matter (OM) introduced in small headwaters is respired preferentially in rivers or is diluted downstream with older material. The delta C-13 and delta N-15 of POM in headwater rivers were heterogeneous and also isotopically distinct from the main stem, suggesting that differences in landscape processes in small catchments impact the concentration and composition of POM in streams. The delta C-13 of dissolved organic matter (DOM) closely mirrored that of POM in the headwaters, with an apparent decoupling of dissolved and particulate OM in the river main stem. The delta C-13 of POM sampled in 2004 had a much different relationship with altitude than observed during previous years: In 2004, a very dry year, we observed enrichment from the headwaters to the main stem, and the opposite pattern in 2002, when rain fell heavily throughout the sampling campaign. This suggests that during dry conditions, in-stream processes ( such as resuspension or photosynthesis) may control riverine POM composition as opposed to terrestrial processes, which dominate during high runoff. Thus a decrease in runoff in Andean headwaters could result in less terrestrial POM transfer to rivers in the Andes foothills and lowland Amazon with a corresponding decrease in aquatic CO2 evasion.
185aaTimes Cited:12 Cited References Count:37
Keywords: amino-acids; atlantic-ocean; carbon; drainage-basin; land-use; nitrogen; particulate; river system; sediments; streams

Chemical composition of the graphitic black carbon fraction in riverine and marine sediments at submicron scales using carbon X-ray spectromicroscopy - Haberstroh, P. R.; Brandes, J. A.; Gelinas, Y.; Dickens, A. F.; Wirick, S. (Geochimica et Cosmochimica Acta, 2006)
id: 1703